Pemberdayaan Kader Posyandu Dalam Mengurangi Stigma Masyarakat Terhadap Penyakit Kusta Di Puskesmas Kinali Kabupaten Pasaman Barat - Masrizal Masrizal; Ane Dayu Perwati; Falah Fauzi; Elvina Apsari; Hanum Salsabila; Nahdah Arifatil Ulfah; Naila Fitri; Naulia Fitratul Afwan; Salsabela Yeni Osandi; Senisa Afrilla Jasra; Zahira Juan Nabilla (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Leprosy remains a global health problem with more than 200,000 new cases each year in the world, and Indonesia ranks third highest after India and Brazil. Community stigma against leprosy is still a major obstacle in the elimination of this disease, including in West Pasaman District, West Sumatra, which recorded 11 cases in the 2023-2024 period. The aim of this activity was to improve the knowledge, attitudes, and actions of posyandu cadres in reducing community stigma towards leprosy through health education and socialization. The method used was a pre-test and post-test design involving 40 posyandu cadres. Data were analyzed using the Wilcoxon test to measure changes in knowledge, attitudes, and actions before and after the intervention. Results showed significant improvement in all variables measured: knowledge (p=0.000; mean 4.90 to 6.85), attitude (p=0.014; mean 2.68 to 3.35), and action (p=0.000; mean 2.43 to 3.25). The discussion shows that education on leprosy recognition and stigma reduction is effective in improving the capacity of posyandu cadres as agents of change in the community. In conclusion, this activity not only improved the cadres' individual skills, but also had a real impact on the community through increased acceptance of leprosy survivors. Similar interventions can be replicated in other endemic areas to strengthen the national leprosy elimination program and promote inclusive and stigma-free communities.